The quality of participation of Brazilian theatre collectives in contexts of community artistic practices. - Cruz, Hugo (2022)
This paper begins with a literature review on participation in the field of community artistic practices. The aim is to identify which is the significant dimensions acting within artistic creation involving professional and non-professional artists from the communities. These elements are then compared with the experience of three Brazilian theatre collectives. Using interviews and focus groups, this study explores creative and organisational group processes and their connection to conceptions of theatre. Our findings suggest that the processes reported by these collectives manifest many of the elements that the literature indicates as fundamental to the quality of participation experiences. These processes seem to promote the development of conceptions of politicised and experimental theatre that give rise to both cultural democratisation and cultural democracy. These conceptions also favour engagement with and perpetuation of high-quality artistic experiences, thus supporting a cycle of community artistic practices.